Aspects du régime parlementaire belge - Fayat, Henri; Ciselet, Georgette; Harmel, Pierre (Bruxelles: Editions de la Librairie Encyclopédique, 1956)
"Henri Fayat; Georgette Ciselet; Pierre Harmel... et al."